2000
DOI: 10.1002/1097-4652(200010)185:1<68::aid-jcp6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Is there a glycosaminoglycan-related heterogeneity of the thymic epithelium?

Abstract: We determined the synthesis and secretion of glycosaminoglycans by three distinct preparations of mouse cultured thymic epithelial cells. These comprised primary cultures of thymic nurse cells (TNCs), which are normally located within the cortex of the thymic lobules, as well as two murine thymic epithelial cells, bearing a mixed, yet distinct, cortico-medullary phenotype. We first identified and measured the relative proportions of the various glycosaminoglycans in the three epithelial cells. Non-sulfated gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Last, it should be noticed that TEC also produce and secrete glycosaminoglycans, including heparan sulfate, and hyaluronic acid, which can also modulate TEC/thymocyte adhesion [53,54].…”
Section: Adhesive Proteinsmentioning
confidence: 99%
“…Last, it should be noticed that TEC also produce and secrete glycosaminoglycans, including heparan sulfate, and hyaluronic acid, which can also modulate TEC/thymocyte adhesion [53,54].…”
Section: Adhesive Proteinsmentioning
confidence: 99%
“…This meshwork of thymic epithelial cells (e.g., the thymic nurse cells) is essential for the proper development of thymocytes into mature lymphocytes. It was demonstrated that subpopulations of these thymic epithelial cells synthesize diVerent GAGs, some secreting high amounts of DS suggesting that a GAG-related heterogeneity exists (Werneck et al 2000). The presence of various DS domains in lymphoid organs might implicate diVerent functional roles for these domains, e.g., related to growth factor binding.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have a mixed phenotype, expressing cortical and medullary TEC markers (Werneck et al . 2000 ). 2BH4 cells were cultivated in 25 or 75 cm 2 culture flasks with RPMI 1640 medium, supplemented with 10% foetal bovine serum (FBS), 1% L-glutamine, and 40 mg/mL gentamicin (all from Invitrogen, Carlsbad, CA, USA) (designated as complete RPMI medium).…”
Section: Methodsmentioning
confidence: 99%